Compact quasi‐elliptic bandpass filter with high selectivity using short‐circuited coupled line. Issue 12 (26th August 2019) - Li, Daotong; Wang, Ju‐An; Liu, Ying; Chen, Zhen; Yang, Lisheng
Abstract: A design strategy of a bandpass filter (BPF) with sharp roll‐off and improved stopband performances is presented in this paper. The proposed filter prototype consists of a couple of parallel‐coupled stepped‐impedance resonators (SIRs) and two short‐circuited coupled lines (SCCLs). The theoretical analysis and numerical simulations on the parallel‐coupled SIRs and coupling structure are carried out. Furthermore, a Butterworth BPF is studied and designed first. By loading the SCCL at the I/O ports of the Chebyshev BPF, four transmission zeros can be introduced beside the passband, which improves the selectivity and stopband performances significantly. For demonstration, a BPF prototype with the center frequency of 2.02 GHz and 3‐dB fractional bandwidth of 5.2% is designed, fabricated, and measured. Moreover, the measured insertion loss is less than 1.5 dB and the rejection levels are larger than 40 dB in both lower and upper stopbands. Thus, the measurement results verify the feasibility of the design.